Sistem Informasi Pengelolaan Arsip Surat Berbasis Web di Kantor Badan Pertanahan Nasional Kota Langsa - Dara Havisha Lamkaruna Dara; liza fitria (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2021)
The rapid development of information technology can benefit almost all fields, both government and private agencies. In an agency always needed a communication that aims to convey information without having to meet directly by means of holding a written communication called a letter. However, currently information technology is very useful to facilitate performance in correspondence activities, especially in the management of mail archives, one of which is at the Langsa City National Land Agency Office. At this time correspondence activities ranging from receiving, scheduling, archiving to verification of incoming and outgoing official letters at the Langsa City BPN Office are still using the agenda book. So with problems like this it takes quite a long time if you want to find the letter file again. From these problems, a system was created that will assist in the management of letter archives at the Langsa City Land Agency Office, namely by grouping letter archives based on letter types consisting of receipts, notifications, invitations and requests. Keywords: Information Systems, Management, Mail